On the biology of Nematinae with hiding larvae (Hymenoptera, Symphyta, Tenthredinidae). - Zinovjev, Alexej Glebovitsch; Vikberg, Veli (Contributions to Entomology = Beiträge zur Entomologie, 1998)
The larvae of Nematinae (Hymenoptera, Tenthredinidae) are usually free-feeding, except for the tribes Hoplocampini, Pseudodineurini, Pristolini, and the following Nematini: Decanematus (= Amauronematus viduatus-group), Pontopristia, the Amauronematus longiserra-group, Polynematus of the subtribe Nematina, the whole subtribe Euurina (Euura and Pontania including the subgenera Phyllocolpa and Eupontania), Micronematus and Sharliphora of the subtribe Pristiphorina, and also the Nearctic genus Neopareophora with an uncertain taxonomic position. Their larvae are either endophytous or otherwise not typically free-living, at least in the earliest stage. The biology of all these sawflies is briefly discussed. It is assumed that Nepionema, which is possibly associated with Rhododendron, also might have hiding larvae at least in early instars. The ovipositing behaviour and gall incitation is described for the leaf-rolling Pontania. Keywords Sawflies, Tenthredinidae, Nematinae, biology, larvae, galls.